Pengaruh Human Relations Terhadap Peningkatan Kinerja Pegawai Di Kantor Kecamatan Lolak Kabupaten Bolaang Mongondow - Mambo, Rully (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstracts: This research background by the problem in organization life, private although government not attention the aspects from the Human Relationship, especially be related to with needless problem the have quality psychology, society and spiritual. This research direction to analyze the influence Human Relationship to increasing employee performance in sub district Lolak. The method used in this research is survey research with the object of research population in this research is the all be related to with Human Relationship application and increasing employee performance in organization at environment sub district Lolak Bolaang Mongondow Regency. The sample taken in this research as much as 65 people employee taken from some office in the sub district Lolak the vertical instance although autonomy instance. Research result to show happen increasing employee performance the consequence from presence Human Relationship as much as 71 % with the other words, that every increase or added 100 scale in variable Human Relationship that increasing employee performance Â can experience Â big increase 71%. Human Relationship have connection functional with increasing employee performance.Â Keywords : Human Relationship, Performance, Employee